Phytophthora pseudosyringae associated with the mortality of Nothofagus obliqua in a pure stand in central‐southern Chile. Issue 6 (11th June 2017) - Fajardo, S. N.; Valenzuela, S.; Dos Santos, A. F.; González, M. P.; Sanfuentes, E. A.
Summary: Mortality of Nothofagus trees in the southern‐central Chile region has been observed for over 30 years. A field survey conducted in 2013 detected partial defoliation and bleeding cankers on Nothofagus obliqua in a pure stand in the Nahuelbuta coastal ranges of the Biobío region. A Phytophthora sp. was isolated from stem cankers and soil samples around symptomatic N. obliqua trees: All isolates were identified as Phytophthora pseudosyringae . These isolates were pathogenic on 1‐year‐old N. obliqua and Nothofagus alpina, and on detached twigs of adult N. obliqua and Nothofagus dombeyi trees. This paper is the first to report association and pathogenicity of P. pseudosyringae with N. obliqua, N. alpina and N. dombeyi native to the Biobío region of Chile. The potential of P. pseudosyringae to cause damage in natural Nothofagus stands in Chile must be determined.